Phytochemical compounds against mild cognitive impairment key proteins: An in-silico approach - Cristian Gonzalez-Ruiz, Isabel Hidalgo, Andrés Portilla-Martínez, Iván Rubio-Gayosso, Hermelinda Salgado-Ceballos, Omar Fabela-Sánchez, Jorge Bernal-Hernández, Miguel Ortiz-Flores (Journal of Applied Pharmaceutical Science, 2025)
Mild cognitive impairment (MCI) is defined as an intermediate stage between normal age-related cognitive decline and pathological cognitive deterioration associated with aging, which course with alterations in one or more cognitive domains and could progress to a major neurocognitive disorder; we investigate five critical proteins involved in the pathophysiological process of MCI: Glycogen synthase 3-β (GSK3β), β-secretase (BACE1), Glutamate transporter associated protein 3–18 (GTRAP3-18), Pregnane X receptor (PXR), and epidermal growth factor receptor (EGFR). We evaluated 2,568 phytochemical compounds as potential ligands of the best conformations of proteins, minimized with 100 ns of molecular dynamics (MDs), which have biological effects on central nervous system disease. All compounds were subjected to virtual screening to obtain the best ligand based on the docking score, then, 1,000 independent docking assays were performed to corroborate the binding site; Root Mean Square Deviation, frequency, and interacting atoms were calculated. Finally, the MD of the best ligand-protein complex was developed. The top probable ligand for each protein was dioscin for BACE1, quadrigeminal-A for GSK3β and GTRAP3-18, psychotridine for PXR and EGFR. This research emphasizes various phytochemicals that influence dysregulated proteins in MCI, offering details on their binding affinities and molecular interactions at the active sites of each receptor.
Keywords: Mild cognitive impairment, phytochemical compounds, virtual screening, molecular dynamics, β-secretase, GSK3β